2016
DOI: 10.1177/1471301214563551
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating access to a diagnosis of dementia: Implications for policies in health and social care

Abstract: The 'Pathways to Diagnosis' study captured the experience of the prediagnosis period of Alzheimer's disease and related dementias through indepth interviews with 29 persons with dementia and 34 of their family caregivers across four sites: anglophones in Calgary, francophones in Ottawa, Chinese-Canadians in Greater Vancouver and Indo-Canadians in Toronto. In this cross-site analysis, we use the 'Candidacy' framework to comprehensively explore the challenges to securing a diagnosis of dementia in Canada and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 62 publications
4
46
0
1
Order By: Relevance
“…SM carried out the interviews and analysis amongst the SHF data set. In re-visiting the data across a series of data sets we conducted what Heaton (2008) refers to as an amplified analysis (Heaton, 2008), and indeed other applications of the Candidacy framework have also utilised secondary data (Koehn et al, 2014). Having team members who are familiar with all the data sets provided useful context but crucially no team member was familiar with all the data.…”
Section: Methodological Considerations and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…SM carried out the interviews and analysis amongst the SHF data set. In re-visiting the data across a series of data sets we conducted what Heaton (2008) refers to as an amplified analysis (Heaton, 2008), and indeed other applications of the Candidacy framework have also utilised secondary data (Koehn et al, 2014). Having team members who are familiar with all the data sets provided useful context but crucially no team member was familiar with all the data.…”
Section: Methodological Considerations and Analysismentioning
confidence: 99%
“…All such negotiations occur in a health care culture where some services are more permeable than others. (Hunter et al, 2013;Klassen et al, 2008;Koehn, 2009;Koehn et al, 2014;Kovandzic et al, 2011;Purcell et al, 2014) which extend the original model and contribute an additional dimension to the challenges of access. Both Koehn and Klassen emphasise the importance of social norms apparent in elder minority ethnic communities on the Candidacy process, and Klassen goes on to demonstrate that these, along with issues of racism and socio-economic disadvantage, construct a series of interrelated barriers to the enactment of Candidacy (Klassen et al, 2008;Koehn, 2009).…”
Section: Candidacymentioning
confidence: 99%
“…Although Koehn et al . () have already focused on the first pre‐diagnosis contacts with health services, we emphasise steps taken, when troubles are not already qualified as requiring medical assistance, as primarily sketched by Krull (). In which conditions does the entourage of the future patient observe that ‘something goes wrong’?…”
Section: The Trouble‐observability‐interpretation Convergencementioning
confidence: 99%
“…Many works address pathways to dementia diagnosis, from a familial perspective (Koehn et al . , Krull ), or a professional perspective (Gove et al . , Hansen et al .…”
Section: Introductionmentioning
confidence: 99%
“…In common with research on candidacy and people with dementia (Koehn et al . ), we found that the process of identification involved not only the individual with ID, but also family, staff and carers. There were reports of reluctance on the part of people with ID to report psychological difficulties, perhaps because of associated stigma, or concerns about worrying friends and family.…”
Section: Resultsmentioning
confidence: 74%